PERAN KOPERASI SEKOLAH DALAM MENGEMBANGKAN JIWA KEWIRAUSAHAAN SISWA DI SMA NEGERI 13 KOTA JAMBI - Rosana Amalia Putri; Andi Sitti Saripah Ainun; Gusti Andre; Fadilla Ulfah; Ahmad Rifki (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
School cooperatives serve as practical-based economic learning media that enhance students’ entrepreneurial abilities. This study aims to describe the role of school cooperatives in developing the entrepreneurial spirit of students at SMA Negeri 13 Kota Jambi. The research employed a descriptive qualitative approach with informants consisting of the cooperative supervisor, student cooperative chairperson, treasurer, active members, and student users of the cooperative services. Data were collected through interviews, observations, and documentation. The findings indicate that the school cooperative plays an important role in fostering students’ creativity, responsibility, communication skills, and independence through activities such as buying and selling, stock management, transaction recording, and customer service. In conclusion, the school cooperative functions as an effective learning medium for cultivating students’ entrepreneurial spirit.